Pertussis in Latin America and the Hispanic Caribbean: a systematic review - Angela Gentile; Lucia Bricks; María L. Ávila-Agüero; Renato Avila Kfouri; Juan Pablo Torres; Rolando Ulloa-Gutierrez; Richard E. Glover; Elsa Sarti (Taylor & Francis Group, 2019)
Introduction: Pertussis in Latin America continues to cause periodic epidemics with substantial morbidity particularly among young children. The disease has persisted despite long-standing vaccination programs in the region. Areas covered: We conducted a systematic review to characterize the recent epidemiology of pertussis in Latin America and Hispanic Caribbean. We undertook a holistic approach and attempted to include all available data concerning pertussis that may explain the changing dynamics of the disease. Expert opinion: There are wide disparities in the reported annual incidence rates of pertussis both within and between countries in the region. General trends in pertussis incidence are difficult to ascertain due to the heterogeneity in the epidemiological data. Available data suggests that the disease burden has changed over the years such that now it predominantly affects those <1 year. Coverage with three doses of the pertussis vaccine has been highly variable, and very few countries have consistently achieved ≥90% coverage annually since 2000. There remain inequalities in vaccination coverage in some regions/localities and specific groups, which sustains the risk of pertussis dissemination. The WHO considers that maternal pertussis immunization provides protection to infants too young to be vaccinated; >10 Latin American countries currently recommend vaccination of pregnant women.